Jesus Christ message to all nations - Jeffs, Warren, 1955- (USA Fundamentalist Church of Jesus Christ of Latter-day Saints, 2013)
A compendium of prophecies attributed to Jesus Christ by Warren S. Jeffs during 2009-2013, principally at Palestine, Texas
"President Warren S. Jeffs, Mouthpiece of God ; Jesus Christ, Author"--4th preliminary page
Keywords: Comparative Theology (3GddGghJ GdebGQfs; Prophecy; Eschatology; Judgment Day; Private revelations; Pedophilia -- Religious aspects